Relationship of cerebrospinal fluid pressure, fungal burden and outcome in patients with cryptococcal meningitis undergoing serial lumbar punctures - Tihana Bicanic (2018)
Objectives: To assess impact of serial lumbar punctures on association between cerebrospinal fluid (CSF) opening pressure and prognosis in HIV-associated cryptococcal meningitis; to explore time course and relationship of opening pressure with neurological findings, CSF fungal burden, immune response, and CD4 cell count. Design: Evaluation of 163 HIV-positive ART-naive patients enrolled in three trials of amphotericin B-based therapy for cryptococcal meningitis in Thailand and South Africa. Methods: Study protocols required four lumbar punctures with measurements of opening pressure over the first 2 weeks of treatment and additional lumbar punctures if opening pressure raised. Fungal burden and clearance, CSF immune parameters, CD4 cell count, neurological symptoms and signs, and outcome at 2 and 10 weeks were compared between groups categorized by opening pressure at cryptococcal meningitis diagnosis. Results: Patients with higher baseline fungal burden had higher baseline opening pressure. High fungal burden appeared necessary but not sufficient for development of high pressure. Baseline opening pressure was not associated with CD4 cell count, CSF pro-inflammatory cytokines, or altered mental status. Day 14 opening pressure was associated with day 14 fungal burden. Overall mortality was 12% (20/162) at 2 weeks and 26% (42/160) at 10 weeks, with no significant differences between opening pressure groups. Conclusion: Studies are needed to define factors, in addition to fungal burden, associated with raised opening pressure. Aggressive management of raised opening pressure through repeated CSF drainage appeared to prevent any adverse impact of raised opening pressure on outcome in patients with cryptococcal meningitis. The results support increasing access to manometers in resource-poor settings and routine management of opening pressure in patients with cryptococcal meningitis. © 2009 Wolters Kluwer Health | Lippincott Williams & Wilkins.